Criss‐cross heart three‐dimensional printed models in medical education: A multicenter study on their value as a supporting tool to conventional imaging. Issue 4 (25th October 2021) - Valverde, Israel; Gomez, Gorka; Byrne, Nick; Anwar, Shafkat; Silva Cerpa, Miguel Angel; Martin Talavera, Maria; Pushparajah, Kuberan; Velasco Forte, Maria Nieves
Abstract: The utility of three‐dimensional (3D) printed models for medical education in complex congenital heart disease (CHD) is sparse and limited. The purpose of this study was to evaluate the utility of 3D printed models for medical education in criss‐cross hearts covering a wide range of participants with different levels of knowledge and experience, from medical students, clinical fellows up to senior medical personnel. Study participants were enrolled from four dedicated imaging workshops developed between 2016 and 2019. The study design was a non‐randomized cross‐over study to evaluate 127 participants' level of understanding of the criss‐cross heart anatomy. This was evaluated using the scores obtained following teaching with conventional images (echocardiography and magnetic resonance imaging) versus a 3D printed model learning approach. A significant improvement in anatomical knowledge of criss‐cross heart anatomy was observed when comparing conventional imaging test scores to 3D printed model tests [76.9% (61.5%–87.8%) vs. 84.6% (76.9%–96.2%), P  < 0.001]. The increase in the questionnaire marks was statistically significant across all academic groups (consultants in pediatric cardiology, fellows in pediatric cardiology, and medical students). Ninety‐four percent (120) and 95.2% (121) of the participants agreed or strongly agreed, respectively, that 3D models helped them to better understand the medical images. Participants scored their overall satisfaction with the 3D printed models as 9.1 out of 10 points. In complex CHD such as criss‐cross hearts, 3D printed replicas improve the understanding of cardiovascular anatomy. They enhanced the teaching experience especially when approaching medical students.